DAKWAH DAN SOSIOLOGI PEMIMPIN - Siti Wahyuni Br Ritonga; Nuramina Pasaribu (STAI DI AL-HIKMAH, 2026)
Da'wah is an important activity in the life of Muslims which functions not only as a means of conveying religious teachings but also as a medium for social development within society. In the context of social and political life, the role of leaders or public officials has a significant influence on the moral, social, and religious conditions of the community. Therefore, the approach to da'wah cannot be separated from sociological studies, particularly the sociology of leadership which examines the relationship between leaders and the people they lead. This study aims to analyze the relationship between da'wah and the sociology of leadership among leaders or officials in shaping a religious and morally grounded society. This research employs a qualitative approach using a literature study method by examining various scientific sources related to da'wah, sociology, and leadership from an Islamic perspective. The results of the study indicate that leaders have a strategic role in supporting the success of da'wah activities within society. Exemplary behavior, policies that support moral values, and the ability of leaders to build effective social communication can strengthen the implementation of da'wah in community life. On the other hand, leaders who lack moral integrity may hinder the effectiveness of da'wah and the development of the Muslim community. Therefore, the integration between da'wah and leadership based on Islamic values is essential to create a harmonious, just, and morally responsible society.